Persian kingship and architecture : strategies of power in Iran from the Achaemenids to the Pahlavis - Babaie, Sussan; Grigor, Talinn (I.B. Tauris, 2015)
"Through analyses of palaces, mausolea, art, architectural decoration and urban design the authors show how architecture was appropriated by different rulers as an integral part of their strategies of legitimising power. They refer to a variety of examples, from the monuments of Persepolis under the Achamenids, the Sassanian palaces at Kish, the Safavid public squares of Isfahan, the Qajar palaces at Shiraz and to the modernisation and urban agendas of the Pahlavis."--Publisher's website